Nanozymes and Nanomaterials in Dairy Technology - Murtadha Abdulhasan Jaafar Aldhalemi (American Journal of Biology and Natural Sciences, 2025)
Dairy Industry is a major sector of the economy that is challenged in the following way. Dairy industry can be relevant to the world food system, as it constitutes a significant source of such nutrients as protein, calcium, and vitamins, which are required to support the health of the population (Yesildemir et al., 2023). This addiction strains the needs of high quality and safety level between the dairy value chain and the raw milk to finished products. However, there are many issues in the industry that require technological improvements (Singh et al., 2023). Some of the dairy industry challenges include food safety threats (microbial contamination), (including E. coli and Salmonella), and chemical contamination (including antibiotics and pesticides), (Chowdhury et al., 2024) and (Yan et al., 2022). Another matter of concern is adulteration, and adding harmful chemicals (such as melamine) that intentionally aims at raising the protein amount is the misdemeanour that is potentially life-threatening (Alizadeh et al., 2023; Luo et al., 2017).